2010
DOI: 10.1111/j.1600-0404.2010.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in elderly subjects: an epidemiological survey in an Italian district

Abstract: Our results confirm that sleep problems are very common in elderly subjects and closely related to medical and psychiatric illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 32 publications
2
39
0
2
Order By: Relevance
“…Of crucial importance is the fact that excessive daytime sleepiness was independently associated with depressive symptoms. This is in agreement with previous reports showing that daytime somnolence is linked with depressive symptoms in the general population (10) and in the elderly (12). Differently from the study of Bixler and cols., metabolic abnormalities were not found to influence excessive daytime sleepiness in diabetic patients (10).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of crucial importance is the fact that excessive daytime sleepiness was independently associated with depressive symptoms. This is in agreement with previous reports showing that daytime somnolence is linked with depressive symptoms in the general population (10) and in the elderly (12). Differently from the study of Bixler and cols., metabolic abnormalities were not found to influence excessive daytime sleepiness in diabetic patients (10).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies indicate that, among the general population, excessive daytime sleepiness has been more strongly associated with depression and obesity than with metabolic factors, sleep-disordered breathing, or sleep disruption (10,11). Interestingly, in elderly people, sleep alterations have been associated with depression, cognitive decline, and diabetes (12). It has also been pointed out that increased daytime sleepiness does not seem to be driven only by the presence of obstructive sleep apnea (OSA).…”
Section: Introductionmentioning
confidence: 99%
“…Almost half of older adults report difficulty in getting to sleep and remaining so (17) . In its turn, an epidemiological study undertaken in a district in Italy (18) (19) , approximately 30% of people aged between 65-79, and 37% aged 80 or over, have loss of hearing capacity. In two studies carried out with Latin-American populations, and based on self-reported data, it was concluded that hearing loss affects 25 -58% of people aged 65 or over (20)(21) .…”
Section: Discussion Of Datamentioning
confidence: 99%
“…Several lines of research (epidemiological surveys, neurophysiological and animal models, studies dealing with -amyloid dynamics) pointed out several correlations between sleep-wake cycle organization and cognitive decline in the elderly, with a particular interest in circadian rhythm alterations and napping behavior [9][10][11].…”
Section: Introductionmentioning
confidence: 99%